Compost liquor bioremediation using waste materials as biofiltration media. - Savage, A. J.; Tyrrel, Sean F. (Elsevier, 2005)
Compost liquor results from the percolation of precipitation through composting waste; the release of liquids from high moisture content feedstocks; and as a result of runoff from hard surfaces and machinery. This research aimed to establish the potential for waste materials to act as media for low-cost compost liquor biofilters. Six types of potential biofilter media were packed into experimental biofilters (1 m long x 0.11 m diameter) and irrigated with compost liquor (organic loading rate of 0.6 kg/m3/d) for three months. The pH, BOD5, NH3/NH4+, and phytotoxicity of the effluent was monitored regularly. Natural, organic materials (oversize, compost and wood mulch) performed best, when compared to synthetic materials such as polystyrene packaging or inert materials such as broken brick. On average, the best media achieved 78% removal of both BOD5 and ammoniacal nitrogen during the study period. Although significant improvements in liquor quality were achieved, the effluent remained heavily polluted.
Keywords: Treatment